Ignacio Eugenio María Andereggen, Introducción a la teología de Tomás de Aquino. Editorial de la Universidad Católica Argentina. Buenos Aires 1992. 208 páginas. ISBN 950-523-007-9 - Sacchi, Mario Enrique (1995)
Fil: Sacchi, Mario Enrique. Armada Argentina. Escuela de Guerra Naval; Argentina